1997
DOI: 10.3319/tao.1997.8.2.239(asee)
|View full text |Cite
|
Sign up to set email alerts
|

Indications of Atmospheric Ozone Decrease in Solar UV-B Flux Changes During the Total Solar Eclipse of 24 October 1995

Abstract: Solar ultraviolet flux measurements in the biological band at 290-320 nm have indicated a sharp increase in the ground reaching solar ultravio let total flux during the recovery phase of the 24 October 1995 solar eclipse event. The flux values came back to their normal control day value within about two hours after the total recovery phase of the eclipse. The solar flux changes at the visible and near infrared wavelengths did not show any such increase in flux except at 600 nm, which is in the Chappius band fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Dolas et al (2002) reported changes in wind speed during the eclipse with minimum value during totality but without much change in wind direction. Niranjan et al (1997) observed sharp increases in the UV flux after the last two hours of contact of the eclipse on 24 October, 1995. These authors attributed the observed increases in groundbased UV flux to the reduction of stratospheric ozone.…”
Section: Introductionmentioning
confidence: 88%
“…Dolas et al (2002) reported changes in wind speed during the eclipse with minimum value during totality but without much change in wind direction. Niranjan et al (1997) observed sharp increases in the UV flux after the last two hours of contact of the eclipse on 24 October, 1995. These authors attributed the observed increases in groundbased UV flux to the reduction of stratospheric ozone.…”
Section: Introductionmentioning
confidence: 88%
“…It may be observed from these figures that the aerosol optical depth decreased from 07:30 hours onwards followed by a gradual increase from 08:10 hours to 09:30 hours and from 09:30 hours onwards it decreased till the end of the eclipse. The post eclipse total optical depths for the remaining period of the day did not show any significant variation in their value (Niranjan et al, 1997a). The aerosol optical depths evaluated for the control day also show no significant variation with time.…”
Section: Resultsmentioning
confidence: 75%
“…The turbidity increases during summer and decreases in monsoon and winter seasons. Niranjan et al (1997) reported that β is maximum in May and minimum in September for this station. This may account for the large variations in correlation coefficients during monsoon for this station.…”
Section: Variation Of Uv-b Irradiance As a Function Of Solar Zenith Amentioning
confidence: 99%